1999
DOI: 10.1016/s0304-3878(99)00012-7
|View full text |Cite
|
Sign up to set email alerts
|

Budget institutions and fiscal performance in Latin America

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
219
0
35

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(265 citation statements)
references
References 17 publications
11
219
0
35
Order By: Relevance
“…Countries with lower transparency issued more debt, and increasing transparency led to the reduction in deficit financing. This finding is consistent with a study of Latin American countries that concluded that greater transparency resulted in lower debt levels and better fiscal discipline (Alesina et al, 1999). Although Benito and Bastida (2009) could not confirm the debt results in their study of OECD countries using a different transparency index, they did find that transparency leads to a balanced budget.…”
Section: Virtues Of Fiscal Transparencysupporting
confidence: 66%
“…Countries with lower transparency issued more debt, and increasing transparency led to the reduction in deficit financing. This finding is consistent with a study of Latin American countries that concluded that greater transparency resulted in lower debt levels and better fiscal discipline (Alesina et al, 1999). Although Benito and Bastida (2009) could not confirm the debt results in their study of OECD countries using a different transparency index, they did find that transparency leads to a balanced budget.…”
Section: Virtues Of Fiscal Transparencysupporting
confidence: 66%
“…budgetary institutions are defined as all rules, regulations, and principles that govern and shape the budgetary process and the relative division of roles, powers, and responsibilities among the various key players involved at each stage of the process. In other words, budgetary institutions include all rules and procedures according to which budgets are drafted, approved, and implemented (Alesina et al, 1999;Allen, Banerji, and Nabil 2004;Gleich 2003;Gollwitzer 2010). Such rules might be either formal (as reflected in constitutions, laws, regulations, manuals, etc.…”
Section: Applications For Practicementioning
confidence: 99%
“…In light of the persistent budget deficits and rising public debt levels in both developed and developing countries, a large amount of research has been accumulated to empirically address whether numerical indices that summarize key aspects of budgetary institutions are correlated with fiscal performance indicators (Krogstrup and Walti 2008;Dabla-Norris et al, 2010). Alesina et al (1999) were the first to formally measure the quality of budget institutions in developing countries by creating an index comprised of ten different components related to different stages of the budgetary process. They found that procedures which include constraints on the deficit and are more hierarchical and transparent lead to lower ratios of primary deficit to GDP.…”
Section: Budgetary Institutions and Fiscal Performance: Empirical Evimentioning
confidence: 99%
“…Participatory budgeting also appealed to middle sectors on the basis of improved efficiency. Some observers might suspect that direct pressure and regional demands would damage administrative capacity by dispersing control over decisions (Alesina et al 1996).18 Efficient allocation of resources, after all, was already difficult in the context of inflation; fiscal surprises, such as economic downturns; and projects that surpassed their expected cost. In Rio Grande do Sul, PB coincided with increased administrative efficiency in terms of the predictability of state spending and revenues.…”
Section: Expanding Across Sectorsmentioning
confidence: 99%